Autopsy evaluation of the implantation site of a His bundle pacing lead demonstrating selective capture. Issue 11 (3rd July 2020) - Kato, Hiroyuki; Igawa, Osamu; Suga, Kazumasa; Murakami, Hisashi; Kada, Kenji; Tsuboi, Naoya; Yanagisawa, Satoshi; Inden, Yasuya; Murohara, Toyoaki
Abstract: Evaluations of His bundle pacing (HBP) lead location at autopsy examination have been rarely reported. We report an autopsy case of a 98‐year‐old man who underwent HBP implantation due to atrioventricular block and heart failure. Although selective HBP was achieved with an acceptable threshold, the stimulus‐to‐QRS interval was relatively longer without correction of the right bundle‐branch block. A macroscopic examination revealed that the HBP lead was inserted on the ventricular side passing through the anteroseptal commissure of the tricuspid valve. Transthyretin cardiac amyloidosis may affect the distal conduction system resulting in a long stimulus‐to‐QRS interval during selective HBP.